Media Rich Instruction - Papa, Rosemary (Springer, 2015)
E-learning has brought an enormous change to instruction, in terms of both rules and tools. Contemporary education requires diverse and creative uses of media technology to keep students engaged and to keep up with rapid developments in the ways they learn and teachers teach.